SOLUTION
From the sequence give
–3, 1, 5, 9, . . .
The first term, a = -3
The common difference, d = 4 (gotten by adding 4 to the next term).
The number of terms required n = 6.
Formula for sum of an arithmetic sequence is given by
![S_n=\frac{n}{2}\lbrack2a+(n-1)d\rbrack](https://tex.z-dn.net/?f=S_n%3D%5Cfrac%7Bn%7D%7B2%7D%5Clbrack2a%2B%28n-1%29d%5Crbrack)
Substituting these values into the equation above we have
![\begin{gathered} S_n=\frac{n}{2}\lbrack2a+(n-1)d\rbrack \\ S_6=\frac{6}{2}\lbrack2\times-3+(6-1)4\rbrack \\ S_6=3\lbrack-6+(5)4\rbrack \\ S_6=3\lbrack-6+20\rbrack \\ S_6=3\lbrack14\rbrack \\ S_6=42 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20S_n%3D%5Cfrac%7Bn%7D%7B2%7D%5Clbrack2a%2B%28n-1%29d%5Crbrack%20%5C%5C%20S_6%3D%5Cfrac%7B6%7D%7B2%7D%5Clbrack2%5Ctimes-3%2B%286-1%294%5Crbrack%20%5C%5C%20S_6%3D3%5Clbrack-6%2B%285%294%5Crbrack%20%5C%5C%20S_6%3D3%5Clbrack-6%2B20%5Crbrack%20%5C%5C%20S_6%3D3%5Clbrack14%5Crbrack%20%5C%5C%20S_6%3D42%20%5Cend%7Bgathered%7D)
Hence, the answer is 42, option B
Answer:
x= -10
Step-by-step explanation:.......
Answer:
To find the x-intercept of any equation, set the y-value to 0.
Step-by-step explanation:
Example:
y=1x+4
To find x-intercept:
0=1x+4
1. Subtract 4 from both sides
2. Divide both sides by 1
The x-intercept is -4
Answer=10
When rounding to the nearest whole number, we need to look to the number in the tenths place
10.09
If the number is 5 or greater, we round up. If the number is 4 or less, we round down.
The number is 0, so we would round down.
10.09 becomes 10
Answer:
Pythagoras’ theorem is a way to find a side or hypothesis when you have 2 sides.
The formula is: a^2 + b^2 = c^2
a and b are sides
c is the hypothesis
<u>Ex: A triangle has a leg that is 5 inches and a leg that is 7 inches. Find the hypothesis using Pythagoras' theorem. </u>
A leg is another way of saying a side.
5^2 + 7^2 = c^2
25 + 49 = x^2
sqrt(74) = sqrt(x^2)
sqrt(74) inches = hypothesis
<u>Ex: A triangle has a leg that is 9 feet and a hypothesis that is 25 feet. Find the other leg using Pythagoras' theorem. </u>
9^2 + b^2 = 25^2
81 + b^2 - 81 = 625 - 81
sqrt(b^2) = sqrt(544)
b = sqrt(554)
Do you understand more?